Analysis of Genetic Mutations Associated with Hereditary Diseases Using PCR and Gene Sequencing Techniques: A Comparative Study among Populations in Southern Iraq - Hassan, Rawaq Taleb; Alawadi, Zahraa Hussein Ali Mahdi; Hassan, Maryam Amer Abdul Mohsen; Radini, Russell Riad (American Journal of Biology and Natural Sciences, 2025)
The genetic architecture of populations from registers of individuals with suspected disorders or congenital malformations in various Middle Eastern countries reveals a characteristic pattern of low complexity apparently-disease-causing variation in exome sequencing data. Such variants are not common in European populations. For example, the population of southern Iraq, which has suffered from major traumas and malnutrition over the last 30 years, yet is clearly underrepresented in databases such as gnomAD. A total of 34 unrelated subjects from the south of Iraq were whole-exome sequenced. The distribution of variants under 500 occurrences and their compositions are comparable to those seen in Arabic exomes from the Middle East. Analysis focusing on frameshift and non-frameshift variants shared within the Iraqi population, but with a maximum occurrence of 4 in the Broad cohort, produces 472 genes, enriched for processes including cell morphogenesis, neurogenesis, and muscle contraction. A subset of genes with 7 or more shared variants includes those previously implicated in blood clots, familial Mediterranean fever, recurrent pregnancy loss, and polycystic kidney disease, in addition to those associated with known SARS-CoV-2 symptoms (HBA1, SLC12A3, and HBB).